On derivations of low dimensional associative dialgebras - Fiidow, Mohamed Abubakar Hagi Mohamed; Rakhimov, Isamiddin Sattarovich; Rikhsiboev, Ikrom M. (AIP Publishing LLC, 2013)
This study introduces a new algorithm for finding derivation of associative dialgebras. The algorithm applied to compute the derivations of low dimensional associative dialgebras. Some simple properties of derivation in terms of left multiplication operators also are provided.